Pengaruh Online Customer Review dan Kredibilitas Influencer terhadap Niat Beli Produk Skincare Brand XYZ di Tiktokshop dengan Customer Trust sebagai Variabel Mediasi - Aryanzah, Tomy Dwi; Myrtanti, Reiny Ditta; Adilla, Nur (SENTRI: Jurnal Riset Ilmiah, 2026)
This study aims to analyze the effect of online customer reviews and influencer credibility on the purchase intention of skincare products Brand XYZ on TikTok Shop, with customer trust as a mediating variable. The research adopts a quantitative approach using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with data collected from consumers who have interacted with skincare products on TikTok Shop. The results show that online customer reviews and influencer credibility have a positive and significant effect on purchase intention, with influencer credibility exerting a stronger influence. Furthermore, both online customer reviews and influencer credibility significantly affect customer trust, indicating their role in reducing consumer uncertainty in social commerce. Customer trust is also proven to have a positive and significant effect on purchase intention. Mediation analysis reveals that customer trust partially mediates the relationship between online customer reviews and purchase intention, as well as between influencer credibility and purchase intention. These findings highlight that consumer trust plays a key role in translating digital information and influencer recommendations into purchase intention. The study contributes to the literature on social commerce by strengthening the application of Signaling Theory in explaining consumer behavior on TikTok Shop and provides practical implications for skincare brands in designing effective digital marketing strategies.